Building capacity for the children's workforce: findings from the knowledge review of the higher education response - Taylor, Imogen; Sharland, Elaine; Whiting, Russell (Learning in health and social care, 2008)
In the UK, there is rapid and far‐reaching policy change designed to provide integrated services to children, young people and their families, linking education, social care, health, youth and community, criminal justice and other professions. Higher education institutions must play a significant role in this process given the large proportion of its graduates who will join the Children's Workforce. In 2007, a University of Sussex team was commissioned by the Higher Education Academy Subject Centres for Social Policy and Social Work; Education; Health Sciences and Practice; Medicine, Dentistry and Veterinary Science; and Psychology, in collaboration with the Children's Workforce Development Council and the Children's Workforce Network to undertake a Knowledge Review of integrated children's services in higher education. In this paper, the authors explore the policy context for integrated children's services and its interaction with the educational and workforce agenda. They set out the process of the Knowledge Review and examine its findings thematically, drawing on activity theory. They suggest that to advance the integrated children's services agenda in higher education, four crucial issues need to be addressed: stakeholders need to provide a clear‐cut business case for investment; universities and regulators must address disciplinary and associated cultural barriers to change at all levels; funders must invest in supporting pilot initiatives and their evaluation; and finally, academics need to find ways to engage and sustain children, young people and their families in the development process.